1994
DOI: 10.1111/j.1365-2036.1994.tb00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic assessment of the intragastric distribution and gastric emptying of an encapsulated drug: the effect of feeding and of a proton pump inhibitor

Abstract: SUMMARYBackground: Local delivery of therapeutic agents to the stomach may be a useful strategy in the treatment of Helicobacter pylori infection. We aimed to see whether the intragastric distribution and gastric retention of a therapeutic agent could be improved, either by giving omeprazole or by dosing after a meal.Methods: Twelve healthy volunteers took part in this double‐blind placebo‐controlled crossover study comparing the effects of omeprazole 20 mg twice daily for 5 days with placebo, and the fasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It has also been suggested that bismuth be administered with meals to enhance it distribution throughout the stomach 59 83 84. The recent clinical trials in China have administered bismuth 30 min before meals.…”
Section: Understanding the Variation In Outcome With Triple Therapy Pmentioning
confidence: 99%
“…It has also been suggested that bismuth be administered with meals to enhance it distribution throughout the stomach 59 83 84. The recent clinical trials in China have administered bismuth 30 min before meals.…”
Section: Understanding the Variation In Outcome With Triple Therapy Pmentioning
confidence: 99%
“…Moreover, in the above study, drugs were given on an empty stomach. Since a meal markedly prolongs gastric residence time of the drug and improves its intragastric distribution to the body and fundus [177], postprandial dosing seems a more suitable strategy for improving topical delivery and mixing (thanks to increased antral motility) of antimicrobials [177,178], provided that binding to or inactivation by food does not occur. An additional finding that would suggest postprandial dosing is that eating is associated with desquamation of gastric surface cells and discharge of mucus [179], possibly exposing the organisms to higher concentrations of the antimicrobial agent, or exposing a higher percentage of the organisms to it.…”
Section: Bowel Preparation For Colorectal Surgerymentioning
confidence: 99%
“…Moreover, in the above study, drugs were given on an empty stomach. Since a meal markedly prolongs drug gastric residence time and improves its intragastric distribution to the body and fundus [58], postprandial dosing seems a more suitable strategy for improving topical delivery and mixing (thanks to increased antral motility) of antimicrobials [58, 59], provided binding to or inactivation by food does not occur. An additional finding that would suggest postprandial dosing is that eating is associated with desquamation of gastric surface cells and discharge of mucus [60], possibly exposing the organisms to higher concentrations of the antimicrobial agent, or may expose a higher percentage of the organisms to it.…”
Section: In Vivo Helicobacter Pylori Eradication Trialsmentioning
confidence: 99%